The preparation of poly(2-hydroxyethyl methacrylate) and poly{(2-hydroxyethyl methacrylate)-co-[poly(ethylene glycol) methyl ether methacrylate]} by photoinitiated polymerisation-induced phase separation in water - Baker, M.; Brown, David; Casadio, Y.; Chirila, T. (Elsevier, 2009)
This paper describes the application of a photoinitiated polymerisation-induced phase separationmethod to the preparation of PHEMA and P[HEMA-co-(MeO-PEGMA)] hydrogels. PHEMA sponges having a morphology of agglomerated polymer droplets and interconnected pores were easily prepared from aqueous mixtures containing HEMA, EDGMA (crosslinker) and DPAP (photoinitiator). P[HEMA-co-(MeOPEGMA)] copolymers having similar morphologies could also be prepared, provided that the proportion of MeO-PEGMA in the copolymer was relatively small. When higher proportions of MeO-PEGMA were used, the resulting polymers were gels rather than sponges, and did not show the sought after droplet/pore morphology. P[HEMA-co-(MeO-PEGMA)] copolymers having higher proportions of MeO-PEGMA and having a morphology of agglomerated polymer droplets and interconnected pores were easily prepared by addition of NaCl to the polymerisation mixture. Thus, incorporation of MeO-PEGMA and adddition of NaCl to the photopolymerisation mixtures provides an easy way of tuning the hydrophilicity of PHEMA copolymer sponges without compromising the desired porous morphology.